2009
DOI: 10.1038/nbt.1566
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive multiplexed analysis of kinase activities and activity-based kinase identification

Abstract: Constitutive activation of one or more kinase signaling pathways is a hallmark of many cancers. Here we extend the previously described mass spectrometry–based KAYAK approach by monitoring kinase activities from multiple signaling pathways simultaneously. This improved single-reaction strategy, which quantifies the phosphorylation of 90 synthetic peptides in a single mass spectrometry run, is compatible with nanogram to microgram amounts of cell lysate. Furthermore, the approach enhances kinase monospecificity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
85
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(89 citation statements)
references
References 58 publications
4
85
0
Order By: Relevance
“…5A), cytoplasm, nucleus, membrane, and cytoskeleton, a distribution consistent with a previous report (40). In comparison with total human proteome (28,612 proteins) and phosphoproteome (11,479 proteins) having GO annotations from Uniprot and PhosphoSitePlus, respectively, the proportions of cytoplasm, nucleus, and cytoskeleton were significantly increased (Fig. 5B).…”
Section: Identifying Direct Substrate Of Erk1 Under the Physiologicalsupporting
confidence: 76%
See 1 more Smart Citation
“…5A), cytoplasm, nucleus, membrane, and cytoskeleton, a distribution consistent with a previous report (40). In comparison with total human proteome (28,612 proteins) and phosphoproteome (11,479 proteins) having GO annotations from Uniprot and PhosphoSitePlus, respectively, the proportions of cytoplasm, nucleus, and cytoskeleton were significantly increased (Fig. 5B).…”
Section: Identifying Direct Substrate Of Erk1 Under the Physiologicalsupporting
confidence: 76%
“…Mass spectrometry has been extensively used for kinasesubstrate interaction mapping (8) and global phosphorylation profiling (9). Although thousands of phosphorylation sites have been detected, complex phosphorylation cascade and crosstalk between pathways make it difficult for large-scale phosphoproteomics to reveal direct relationships between protein kinases and their substrates (10,11). Extensive statistics, bioinformatics, and downstream biochemical assays are mandatory for the substrate verification (12,13).…”
mentioning
confidence: 99%
“…Then, to seek proteins that showed a high correlation with LO-hydrolyzing activity, all proteins in the fractions were identified and quantified by LC-MS/MS analysis. Theoretically, protein of a higher correlation coefficient has higher probability of a responsible protein to the activity profile, and our previous experiences (Kubota et al, 2009;Sakurai et al, 2013, and unpublished results) are in agreement with this concept. In total, 2381 proteins were identified, but there was no single protein that had the bimodal chromatographic peaks highly correlated with the enzyme activity profile (data not shown).…”
Section: Enzymatic Lo Hydrolysis In Human Pulmonary Subcellularsupporting
confidence: 77%
“…is usually required to achieve the purification. On the other hand, we have recently extended an advanced methodology named proteomic correlation profiling to identify drug metabolizing enzymes (Sakurai et al, 2013), whose basic concept was previously reported by Kubota et al (2009). In this methodology, the biologic material is fractionated by column chromatography, followed by the calculation of each protein's correlation coefficient between the enzyme activity and proteomic profile of the fractions.…”
Section: Introductionmentioning
confidence: 99%
“…Large-scale phosphoproteomics, however, does not typically reveal precise connections between protein kinases and their direct substrates (11,12). In recent years, there have been increasing attempts to develop mass spectrometry-based proteomic strategies for the identification of elusive kinase substrates (7,13,14).…”
mentioning
confidence: 99%